Pengembangan Aplikasi Pecinta Baca Buku Menggunakan Google Cloud Artificial Intelligence Berbasis iOS - Hario Budiharjo; Achmad Arwan; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Public Library visitors in the Jakarta area are less than 500 thousand visitors per year based on data from the Jakarta Open Data, even though the population in the city of Jakarta has less than 10 million inhabitants. When compared to the National Library of Singapore which had 26 million visitors in 2017 based on data from the National Library of Singapore website, the number of visitors to the Jakarta Regional Public Library is very small. This does not mean that Indonesians are not interested in reading. Indonesians who are interested in reading books using digital books, even 500 people line up to borrow a digital or electronic book at the National Library of Indonesia. Due to the above problems, an iOS-based application was created for the process of reading books with features that support reading books. In research that uses Google's cloud artificial intelligence to listen to books in the application, Forums for users to discuss books to be discussed and Challenge to test their knowledge of books they have read. The result of developing an application based on iOS 24 needs. Researchers conducted white-box testing using unit testing and integration which produced a value of 100% and black-box testing using validation testing which resulted in a value of 100%. From the test results it can be interpreted that the application works in accordance with defined needs.